2013
DOI: 10.1093/nar/gkt1011
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and EGCG bind directly and distinctively to miR-33a and miR-122 and modulate divergently their levels in hepatic cells

Abstract: Modulation of miR-33 and miR-122 has been proposed to be a promising strategy to treat dyslipidemia and insulin resistance associated with obesity and metabolic syndrome. Interestingly, specific polyphenols reduce the levels of these mi(cro)RNAs. The aim of this study was to elucidate the effect of polyphenols of different chemical structure on miR-33a and miR-122 expression and to determine whether direct binding of the polyphenol to the mature microRNAs (miRNAs) is a plausible mechanism of modulation. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 29 publications
1
78
0
1
Order By: Relevance
“…Interestingly, studies have also shown that EGCG can bind to both DNA and RNA molecules [55, 56]. Using 1 H NMR spectroscopy, one study found that EGCG modulates miR-122 and miR-33 by direct binding to the miRNAs [57]. Together these findings suggest multiple possible mechanisms by which EGCG can modulate miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have also shown that EGCG can bind to both DNA and RNA molecules [55, 56]. Using 1 H NMR spectroscopy, one study found that EGCG modulates miR-122 and miR-33 by direct binding to the miRNAs [57]. Together these findings suggest multiple possible mechanisms by which EGCG can modulate miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, polyphenols may bind to miRNAs directly. Resveratrol and EGCG were shown to bind to miRNAs directly by 1 H NMR spectroscopic method (Baselga-Escudero et al, 2014). EGCG bound stronger to miR-122 than to miR-33a through an interaction with all of the rings in the molecule, while resveratrol bound equally to miR-33a and miR-122 primarily through an A ring interaction (Baselga-Escudero et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol and EGCG were shown to bind to miRNAs directly by 1 H NMR spectroscopic method (Baselga-Escudero et al, 2014). EGCG bound stronger to miR-122 than to miR-33a through an interaction with all of the rings in the molecule, while resveratrol bound equally to miR-33a and miR-122 primarily through an A ring interaction (Baselga-Escudero et al, 2014). Persimmon tannin, which contained high content of EGCG and ECG in the extension units, might regulate miR-122 and miR-33b levels by direct binding, which could modulate miRNA stability or degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Some M A N U S C R I P T ACCEPTED MANUSCRIPT 19 authors suggeated that, polyphenols may bind to miRNAs directly. For example, resveratrol and EGCG were shown to bind to miRNAs directly by 1 H NMR spectroscopic method [39]. However, Lin et al [40] proposed that miR-27 might not directly repress PPARγ or C/EBPαin 3T3-L1 cells, but target an unknown gene that negatively regulates the two key transcription factors (PPARγ and C/EBPα) of adipogenic differentiation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Current data suggested that grape proanthocyanidin extracts, EGCG [39] and cocoa proanthocyanidins [41], differed in their effects on modulating expression of miRNAs. These results and our current data suggested that the effects of polyphenols on miRNAs expression were structure-dependent.…”
Section: Accepted Manuscriptmentioning
confidence: 99%